Penerapan Teknik Sinematografi oleh Director Of Photography pada Produksi Video Feature “Jejak Rasa: Akar dari Tanah Priangan” - Diya Mirzha Rusyanto; Fazila Safia Utomo; Rinda Aunillah Sirait; Kurnia Lucky Fadillah (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2026)
IIn the process of creating the feature video "Jejak Rasa: Akar dari Tanah Priangan," the author serves as the Director of Photography, responsible for managing the visual aspects to effectively and comprehensively convey the message. This is achieved through the application of various cinematographic techniques, such as careful selection of camera angles, types of shots, camera movements, and in-depth composition. The main goal of this feature video production is to showcase the cultural value of cassava as an essential part of the culinary identity of Tanah Priangan, while also highlighting its transformation from traditional food to modern culinary innovation with contemporary relevance and appeal. This work is expected to provide a more comprehensive visual representation of local food culture and raise public awareness about the importance of preserving culinary heritage as part of the nation's cultural wealth. The application of cinematographic techniques used not only strengthens the delivery of information but also effectively enhances the aesthetic quality of the work as a visual communication medium that can impact the audience emotionally and intellectually.